1996
DOI: 10.1074/jbc.271.50.32112
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide Biosynthesis in Rhizobium leguminosarum

Abstract: The lipopolysaccharide of Rhizobium leguminosarum differs from that of other Gram-negative organisms. R. leguminosarum lipid A lacks phosphate groups, but it contains a galacturonic acid residue at the 4-position and an aminogluconate moiety in place of the usual glucosamine 1-phosphate unit. R. leguminosarum lipid A is esterified with a peculiar long chain fatty acid, 27-hydroxyoctacosanoate, not found in enteric Gramnegative bacteria, and the inner core of R. leguminosarum contains mannose and galactose in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(96 citation statements)
references
References 27 publications
6
90
0
Order By: Relevance
“…In accordance with Carlson's structure, we have been able to identify three novel glycosyltransferases unique to extracts of R. leguminosarum that incorporate mannose (23), galactose (23), and the outer Kdo (present study) in the expected order ( Fig. 2) to the conserved lipid A precursor, Kdo 2 -lipid IV A .…”
supporting
confidence: 86%
See 2 more Smart Citations
“…In accordance with Carlson's structure, we have been able to identify three novel glycosyltransferases unique to extracts of R. leguminosarum that incorporate mannose (23), galactose (23), and the outer Kdo (present study) in the expected order ( Fig. 2) to the conserved lipid A precursor, Kdo 2 -lipid IV A .…”
supporting
confidence: 86%
“…E. coli is unable to catalyze these core glycosyltransferase reactions, which are characteristic of extracts of R. leguminosarum (23). Accordingly, E. coli membranes prepared from strains containing the vector pET23a alone did not catalyze efficient GDP-mannose, UDP-galactose, or CMP-Kdo-dependent band shifts of Kdo 2 -[4Ј-32 P]lipid IV A (or related glycolipids) in our assays (Fig.…”
Section: Sequential Addition Of Mannose Galactose and Kdo To The Acmentioning
confidence: 71%
See 1 more Smart Citation
“…The R. leguminosarum lpxE structural gene encoding the 1-phosphatase has recently 2 M. Karbarz and C. R. H. Raetz, manuscript in preparation. (43,44,(55)(56)(57). The only exceptions are the reactions that incorporate the 4Ј-galacturonic acid and the ␤-hydroxybutyrate residues.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of this common lipid A precursor also implied that these rhizobial cells possess unique enzyme activities, which process their Kdo 2 lipid-IVa analog into the mature rhizobial lipid A structure. Several of these enzyme activities have been reported, including a membranebound phosphatase that removes the 4Ј-phosphate from Kdo 2 lipid-IVa and requires the presence of the Kdo residues for maximum activity (21), a second phosphatase that removes the 1-phosphate (22), and a unique acyl carrier protein required for the transfer of the 27-hydroxyoctacosanoyl residue to the lipid A (23). In addition, a rhizobial-specific mannosyl transferase activity has been identified that transfers mannose from GDPMan to Kdo 2 lipid-IVa (24).…”
mentioning
confidence: 99%